United Nations sphere of education: the publication on Kazakhstan Mass Media (Herald of Journalism, 2018)
The given article is about publication of United Nations education sphere issues, also influence of Mass Media on resolutioning those issues, modelling public opinion, therefore dealing the issue by basical materials that published on Kazakhstan Mass Media, supporting international colloboration on education, science and culture matters, as well as evaluating possibility of spreading on local Mass Media the information about main projects done by UN, and point some problems in it.Key words: Standards of international education, universal education, intellectual and moral qualities, strategic development.